Characterization of Carboxylated Cellulose Nanocrystals Isolated Through Oxalic Acid Hydrolysis from Solid Residues of Softwood-Derived Glycol Lignin Production - Thi Thi Nge; Tatsuhiko Yamada (Molecules, 2025)
The efficient use of renewable lignocellulosic biomass has attracted wide interest, as it promises to reduce the environmental impact of fossil fuel consumption. A recently developed batch-scale process, which produces glycol lignin (GL) from softwood biomass, generates a considerable amount of cellulose-rich solid residues (SRs) as a byproduct. In this study, usable cellulose was isolated from SRs in the form of carboxylated cellulose nanocrystals (O-CNCs). The properties of O-CNCs were investigated to establish a possible integrated biomass utilization system based on the GL production technology. Three different forms of purified SRs—never-dried (N-Cel), freeze-dried (F-Cel), and vacuum-dried (V-Cel) cellulose—were subjected to oxalic acid (OA) hydrolysis at 95 °C for 4 h. The average length of O-CNCs ranged from 90 to 120 nm and the height ranged from 3 to 6 nm for separate particles and from 8 to 20 nm for aggregates. The carboxyl group content was 0.11–0.23 mmol/g O-CNCs. The overall results indicated that the yields, dimensions, surface charges, and thermal stability of the O-CNCs were largely influenced by the nature of the starting cellulose. In addition, O-CNCs prepared from recycled OA exhibited similar properties to those prepared from fresh OA.